Corporation José R. Lindley: Balanced Scorecard implementation - Jáuregui Machuca, Kety Lourdes; Santana Ormeño, Jorge Martín (Universidad del Rosario, 2008)
José R. Lindley Corporation is one of the most important organizations that operates in the country with a prestigious tradition in the market of sodas trough its leader brand “Inca Kola”. This enterprise has as its main character keeping in the vanguard of the sector, demonstrating a high competitive level in the recent years. With the aim of keeping its leadership, facing successfully the diffi cult environment of the local market and entering international markets, José R. Lindley Corporation has constantly worried about incorporating management philosophies and tools that allow guaranteeing its sustainability in the time with a vision about the future. In this sense, it decided to implement a Balanced Scorecard (BSC), as a tool to measure and improve its productivity and effi ciency, in the framework of its corporative strategy. In other words, the BSC facilitated monitoring the degree of accuracy in the implementation of its strategy. In this context, the case illustrates how the process of the implementation of a BSC in José R. Lindley Corporation was performed, showing the complexity of the process that involved fi nancial resources and an important dedication of the organization, specially those ones who comes from the High Direction and the Information Systems Area to provide technological support. In addition, the case shows how it is possible to translate a strategy into a group of objectives and specifi c measures trough the BSC. Based on the cause-effect relation, it links the objectives with its respective indicators, strategic initiatives and corresponding plans of action.

La Corporación José R. Lindley es una de las organizaciones más importantes que operan en el país, con una prestigiosa trayectoria en el mercado de gaseosas a través de su marca líder Inca Kola. Esta empresa se ha caracterizado por mantenerse a la vanguardia del sector, el cual en los últimos años se ha mostrado altamente competitivo. Con la finalidad de mantener su liderazgo, hacer frente con éxito al difícil entorno del mercado local e incursionar en nuevos mercados internacionales, la Corporación José R. Lindley se ha preocupado constantemente por incorporar fi losofías y herramientas de gestión que le permitan asegurar su sostenibilidad en el tiempo, con una visión de futuro. En este sentido, decidió implementar un Balanced Scorecard (BSC), como una herramienta para medir y mejorar su productividad y efi ciencia, en el marco de su estrategia corporativa. En otras palabras, el BSC le facilitó monitorear el grado de acierto en la puesta en marcha de su estrategia. En este contexto, el caso ilustra cómo se realizó el proceso de implementación de un BSC en la Corporación José R. Lindley, mostrando la complejidad del proceso que involucró recursos fi nancieros y una dedicación importante de la organización, en especial provenientes de la Alta Dirección y del área de Sistemas de Información para el Soporte Tecnológico. Asimismo, el caso muestra cómo es posible traducir una estrategia en un grupo de objetivos y medidas concretas, a través del BSC. En función a la relación causa-efecto, vincula los objetivos, con sus respectivos indicadores, iniciativas estratégicas y planes de acción correspondientes.
Keywords: Balanced Scorecard; Soda’s sector; Cuadro de mando integral; Implementation of the strategy; Sector de bebidas gaseosas; Implementación de la estrategia; Performance indicators; Indicadores de desempeño; https://purl.org/pe-repo/ocde/ford#5.02.04